Escalonamento de tarefas e fluxos de comunicação para sistemas semi-particionados em arquiteturas NoC - Bonilha, Iaê Santos (2014)
Despiste the fact that many scheduling models teoretically capable of high system resource utilization were proposed with the development of the real-time system, the industry still uses the first scheduling model proposed for multi-processor real-time systems, the partitioned scheduling model. This scheduling model can guarantee scheduling of task sets up to around 69% processor utilization, which falls pale in comparison to recent scheduling models that can guarantee scheduling up to 97% processor utilization. The motive behind the utilization of the partitioned scheduling as industrial model is the amount of studies made on this model and the development of scheduling analysis capable of providing temporal guarantees for this model on a real system environment. Recent scheduling models, like semi-partitioned scheduling, offer the possibility of a higher system resource utilization, it still lack studies and scheduling analysis capable of provide temporal guarantees under a real environment. The current scheduling analysis for most of the more recent models take advantage of a series of abstractions, failing to provide guarantees under real circumstances. This papers primary objective is to produce a new scheduling analysis for semi-partitioned scheduling, capable of achieving temporal guarantees taking some of the previously abstracted factors, like task communication and the impact f task migration on its communications flows, approximating the scheduling model to real environmental conditions. With the development of such analysis preliminary studies were made on heuristic task mapping algorithms for semipartitioned systems.